Transnational Finnish Mobilities : proceedings of FinnForum XI - Leinonen, Johanna; Kostiainen, Auvo (Siirtolaisuusinstituutti, 2019)
This volume is based on a selection of papers presented at the conference FinnForum XI: Transnational Finnish Mobilities, held in Turku, Finland, in 2016. The twelve chapters discuss two key issues of our time, mobility and transnationalism, from the perspective of Finnish migration. The volume is divided into four sections. Part I, Mobile Pasts, Finland and Beyond, brings forth how Finland’s past – often imagined as more sedentary than today’s mobile world – was molded by various short and long-distance mobilities that occurred both voluntarily and involuntarily. In Part II, Transnational Influences across the Atlantic, the focus is on sociocultural transnationalism of Finnish migrants in the early 20th century United States. Taken together, Parts I and II show how mobility and transnationalism are not unique features of our time, as scholars tend to portray them. Even before modern communication technologies and modes of transportation, migrants moved back and forth and nurtured transnational ties in various ways. Part III, Making of Contemporary Finnish America, examines how Finnishness is understood and maintained in Contributors 1. Introduction: On Transnationalism and Mobility / Johanna Leinonen I MOBILE PASTS, FINLAND AND BEYOND 2. Hard Times and Tough People, but You May Have to Go / Petri Minkkinen 3. Recalling – Reconstituting – Migration: Sámi Americans and the Immigrant Experience / Thomas A. DuBois 4. Migrant Workers, Refugees, or War Brides? Finnish Women in the Third Reich and Occupied Germany / Anu Heiskanen II TRANSNATIONAL INFLUENCES ACROSS THE ATLANTIC 5. Music and Migration: John Rosendahl as a Musical Entrepreneur in the United States in the 1920s and Early 1930s / Saijaleena Rantanen 6. A Finnish Narrative of the Manufacturing Industry in the Midwest in the Mid-1930s / Elianne Riska 7. Sports in Constructing Finnish Americanness in Terms of Transnational and Regional Identity in Two Finnish American Literary Texts / Roman Kushnir III MAKING OF CONTEMPORARY FINNISH AMERICA 8. From a Joke ...